Referral situation from a municipal hospital with general practitioner: a cross-sectional study - Agrawal, Pawan Kumar Bajaj; Gupta, Priyanka; Parajuli, Suraj (Journal of General Practice and Emergency Medicine of Nepal, 2023)
Introduction: Referral rate is an important measure of performance of a healthcare institution. Analysis of referral trend helps institutions to understand their care delivery needs and plan accordingly. General practitioners (GPs) have an important role in strengthening municipal primary healthcare service. Referral pathway in Nepal has improved since the implementation of national health insurance program. This study aimed to reflect upon the referral trend from a GP led municipal hospital in Nepal. Method: The study was carried out in the out-patient department of Amppipal, a municipal hospital in Gorkha over a duration of one year. Decision for necessity of referral was made by the practicing GP. Referral rate, proportion of referral who were insured, proportion of referral based upon clinical decision compared to patients’ request and specialist-wise referral was calculated. Result: The total number of patients’ visits in OPD was 20,136. The referral percentage from OPD was 2.9%. Out of the total referrals, 95.6% were insured by national health insurance program. Only 59% percent of referrals had clinical indication for further diagnosis and/or treatment and the rest 41% requested for referral by themselves. Eighty-eight percent of referred patients were satisfied with the treatment outcome at higher center. Orthopedics (16.1% of total referred cases) was one of the mostly sought for specialists followed by ophthalmology (15.1%) and cardiology (10.5%). Conclusion: Our study presented the referral trend in a GP led primary care hospital in Nepal. Government health insurance program has necessitated proper recording of referral, thereby strengthening referral pathway in national healthcare system. Regular analysis of referral could help in understanding the performance and needs of a healthcare institution.